(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Polytrauma remains one of the most challenging conditions in emergency and surgical practice due to the combination of multiple life-threatening injuries and rapidly developing physiological instability. This article provides an overview of modern surgical management algorithms for polytrauma patients, focusing on the principles of damage control surgery, timing of interventions, prioritization of life-saving actions, and integration of resuscitation strategies with operative steps. Emphasis is placed on early identification of critical injuries, staged surgical decision-making, and individualized approaches based on trauma severity, hemodynamic stability, and physiological reserve. The article highlights how contemporary surgical tactics aim to minimize the lethal triad of hypothermia, acidosis, and coagulopathy while maximizing patient survival and functional recovery.